Marketing Capabilities for Downstream Adoption - Deutsch,Julius Karl; Matovinovic,Gero Adrian (2026)
In complex B2B value chains, even functionally strong innovations may struggle when success depends on end-consumer adoption beyond the focal firm’s direct control. This thesis examines how context-specific market conditions shape perceived adoption drivers and barriers, how these perceptions influence downstream adoption, and how B2B firms can respond by adapting marketing capabilities to shape downstream adoption perceptions. It focuses on FMCG-related value chains, where end-consumer perceptions affect not only final demand but also the willingness of other downstream actors like producers and retailers to invest in and support an innovation. Building on existing literature, this thesis develops a framework connecting market context, perceived adoption drivers and barriers, downstream willingness to adopt, and B2B firm-side marketing capabilities. The framework is empirically examined and refined through a mixed-method single-case study in collaboration with a global packaging company, drawing on an expert interview, focus groups, and a survey in the context of prepared food packaging. The findings indicate that adoption is not determined by product characteristics alone but depends on the fit between market context, perceived value, and firm-side responses. Context did not play an equal role across all dimensions. Some contextual factors and perceived drivers or barriers appeared more influential than others, while markets appeared more similar than expected. This underlines the need to identify which factors are actually relevant for adoption and where potential mismatches may occur between what the innovation offers, how it is marketed, and what end-consumers value, expect, or trust. Theoretically, this thesis strengthens the link between marketing and strategic management research. Practically, the refined framework helps managers map adoption drivers and barriers, distinguish relevant contextual differences, and identify suitable marketing capability responses in retail-oriented industries.
Keywords: marketing capabilities; B2B value chains; downstream adoption; consumer perceptions; market characteristics